X-ray subletal irradiation of murine 3T3 fibroblasts for feeder-layer - Ramírez-Téllez, Andrea (2015)
Keratinocytes, the main cells of the epidermis, require mitotically inactive but live feeder-layer cells for their survival and proliferation. We evaluated four X-ray irradiation doses on 3T3 murine fibroblasts for feeder-layer production. Each dose effect was evaluated by cell counting and cellular viability determination (MTT), cell adhesion (plating efficiency) and cell migration (scratch wound healing). Mitotic arrest was suggested by nuclear staining (GIEMSA). We determined that an 80 Gy X-ray dose generated enough cell damage to cause mitotic arrest yet keeping metabolically active cells up to 25 days.